Hematopoietic Stem Cell Transplantation for Acute Myeloid Leukemia - Silla, Lucia Mariano da Rocha; Ikoma-Colturato, Maura Rosane Valeria; Funke, Vaneuza Araujo; Pitombeira, Beatriz Stela Gomes de Souza; Paton, Eduardo Jose de Alencar; Hamerschlak, Nelson; Arantes, Adriano; Astigarraga, Claudia; Barroso, Karine Sampaio Nunes; Beltrame, Miriam Perligeiro; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
This summary is intended to update the Brazilian Society of Bone Marrow Transplantation and Cellular Therapy (SBTMO) 2020/1 consensus on HSCT for Acute Myeloid leukemia (AML).